Compromis et patrimoine : les zones humides rétro-littorales face aux changements globaux - Clémence Dedinger; Christophe Boschet; Clarisse Cazals; Nathalie Long; Audrey Rivaud (Développement Durable et Territoires)
Inspired by social ecological economics approaches, this article investigates compromises through heritage to understand environmental governance. Bridging theories of conventions and practices, it draws evidence on their creation considering the relationship between actors’ representations of heritage, practices and their embeddness into relational systems. We apply this framework to two retro-littoral marshes in Charente-Maritime, having use and preservation issues renewed by flooding risk. It provides mechanisms of wetland socio-ecosystems’ potential to adapt, opening perspectives for identifying territories’ trajectories facing those issues.